Defining Success in Transitions from Pediatric to Adult Chronic Pain Care: A Descriptive Qualitative Study of Perspectives of Young Adults Living with Chronic Pain. Issue 7 (19th April 2022) - Oreper, Julie; Khalid, Ayesha; Sheffe, Sarah; Mustafa, Nida; Vader, Kyle; Bosma, Rachael
Abstract: Objective: To explore how young adults with chronic pain define a successful transition from pediatric to adult chronic pain care and how they would like to be empowered to achieve a successful transition. Design: A descriptive qualitative design. Setting: Participants were recruited from a hospital-based chronic pain clinic in Toronto, Canada, and through social media. Subjects: Young adults (18–25 years of age, inclusive) who received chronic pain care in a pediatric setting and continued to self-identify as having a need for chronic pain care in an adult chronic pain care setting. Methods: Semistructured interviews were used to understand the perspectives of young adults with chronic pain. Interviews were audio-recorded, transcribed verbatim, and checked for accuracy. Qualitative inductive content analysis was used to analyze the interview data. Results: Eight young adults with chronic pain were interviewed (all women; median age=19 years). Five themes that addressed the study objectives are described: 1) Young adults value skill-building and knowledge about the transition, 2) establishment of a strong therapeutic alliance with health care providers, 3) coordinated and planned transition, 4) social and environmental support, and 5) respect for young adults' independence and autonomy. Conclusion: Findings suggest the need for a collaborative and individualized approach to the successful transition of young adults across the continuum of chronic pain care that addresses their unique needs. To promote successful transition, clinicians should build relationships with young adults that facilitate choice and autonomy while enhancing skill-building and education on available resources.